Визначення задач контекстної класифікації відео для потреб бізнес-аналізу та реінжинірингу - Новічонок, М. С. (ХНУРЕ, 2024)
This work is devoted to defining tasks of the context video classification for business analysis and reengineering needs. The current state of using computer vision methods in enterprises was considered. The main requirements to the system based on the video classification to perform business analysis tasks are defined. The relation between business analysis and reengineering goals, related business studies and their common quality criteria is shown. The processes and their characteristics that could be potentially classified using the context classification methods are advised
Keywords: реінжиніринг; класифікація відео